Biohemijski efekti personalizovanih kliničkih intervencija na hepatorenalnu funkciju, imuni odgovor, i inflamatorni markeri kod pacijenata sa infekcijama: Hepatorenal–Immune Biomarker Changes - Li, Ying; Zhou, Ying; Zhang, Jie; Li, Yi; Liu, Xin (Journal of Medical Biochemistry, 2025)
Background: Hepatic and renal dysfunction, immune imbalance, and excessive inflammatory activation are common complications in postoperative infections. This study evaluated the biochemical effects of personalized clinical interventions on hepatorenal function, immune responses, and inflammatory cytokines in infected patients. Methods: A total of 110 patients with postoperative infections admitted between January 2023 and January 2025 were randomly assigned to an experimental group or a control group (n = 55 each). The control group received standard clinical care, while the experimental group underwent additional individualized intervention measures. Serum hepatic (AST, ALT) and renal (BUN, SCr, UA) biochemical markers, T-lymphocyte subsets (CD3⁺, CD4⁺, CD8⁺), inflammatory factors (IL-6, CRP, TNF-α), and SF-36 quality-of-life scores were assessed before and after intervention. Adverse events were recorded. Results: Post-intervention, AST and ALT levels were significantly lower in the experimental group compared with the control group (P < 0.05). BUN, SCr, and UA were also significantly reduced after individualized intervention (P < 0.05). The experimental group demonstrated higher CD3⁺ and CD4⁺ levels and lower CD8⁺ levels than the control group (P < 0.05). Levels of IL-6, CRP, and TNF-α were markedly decreased in the experimental group (P < 0.05). Quality-of-life scores across all domains were significantly higher following individualized intervention (P < 0.05). The incidence of adverse reactions was notably lower in the experimental group (5.45% vs. 20.00%; χ² = 4.010, P = 0.045). Conclusion: Personalized clinical interventions significantly improved hepatic and renal biochemical indices, enhanced immune function, and reduced systemic inflammatory cytokines in patients with postoperative infections. These findings support the integration of individualized strategies into infection management to optimize biochemical and clinical outcomes.